EXTH-13. LOCAL DELIVERY OF AN IL-15 SUPERAGONIST USING A REPLICATING RETROVIRUS SIGNIFICANTLY IMPROVES SURVIVAL AND LYMPHOCYTE INFILTRATION IN POORLY IMMUNOGENIC MURINE GLIOBLASTOMA MODELS. (12th November 2021) - Haddad, Alexander; Spatz, Jordan; Montoya, Megan; Collins, Sara; Gill, Sabraj; Wang, Elaina; Chuntova, Polly; Young, Jacob; Kasahara, Noriyuki; Aghi, Manish K
Abstract: Glioblastoma (GBM) leads to severe systemic and local immunosuppression, and immunotherapies have had limited clinical success. Here, we evaluated the treatment efficacy of RLI, a superagonist of T-cell activator IL-15, delivered to tumor cells using a tumor-selective retroviral replicating vector (RRV) in the syngeneic murine SB28 and Tu2449 GBM models, which are both engineered to be poorly immunogenic with low-mutational burden and known resistance to immunotherapy, and hence more accurate biomimetic models of human GBM. RRV-RLI replicated and spread effectively in cultured murine GBM cells with robust production of functional RLI (165.4 ± 5.3 ng/mL). Stereotactic injection of RRV-RLI into pre-established intracerebral SB28 tumors significantly reduced tumor growth on bioluminescent imaging, and increased median survival compared to control mice (55 vs. 19 days, p=0.002), leading to long-term survival in 12% of treated mice. In the Tu2449 model, imaging results showed complete eradication of intracerebral tumors after RRV-RLI treatment, with long-term survival (median not reached) in > 85% of treated mice, compared to a median survival of 12.5 days in control mice (p=0.001). RRV-RLI treated tumors showed significantly increased CD8 T-cell infiltration, without altering immunosuppressive cell populations. Similarly, broad anti-tumor inflammatory changes, including increased expression of genes involved in T-cell activation and killing, were observed in the NanoString nCounter platform using a 770-gene panel representing various immune cell types. Notably, RLI was not detected in the blood of treated mice, and tumor-localized RRV-RLI gene delivery showed no adverse systemic immune effects in either model. In summary, RRV-mediated RLI immunotherapy results in immunostimulatory and pro-inflammatory changes to the tumor microenvironment and achieves a significant survival benefit in two poorly immunogenic syngeneic murine models of GBM. This tumor-localized immunomodulatory gene therapy has the potential to safely reverse the T-cell depleted immunophenotype of GBM.